1963
DOI: 10.1017/s0022172400020775
|View full text |Cite
|
Sign up to set email alerts
|

Sources of staphylococcal infection in surgical wound sepsis

Abstract: There are, broadly, two ways of controlling post-operative staphylococcal wound sepsis. One is to take every possible precaution against every conceivable mode of infection. Attempts to do this are undoubtedly effective, and it is sometimes the only way of dealing quickly with a severe outbreak. But it is expensive of time, money, and temper and is so tedious that when the emergency is over, its complicated routine tends to degenerate into an ineffective ritual. Another defect of this method is that it encoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1963
1963
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…A significant correlation has been found by some investigators (Williams et al 1959;Colbeck, 1960;Burke, 1963), but others (Rogers et al 1965;Browne et al 1959;Bullock et al 1964) have not. Williams et al (1959), Weinstein (1959), McNeill, Porter & Green (1961, Williams et al (1962), Ketcham et al (1962), Lindbom, Laurell & Grenvik (1967) and a, b) reported a higher incidence of wound sepsis among carriers, but Rogers et al (1965), Bullock et al (1964), Browne et al (1959, Lowden, Vaithilingham & Milne (1962), Bassett et al (1963 and Moore & Gardner (1963) did not find this to be true.…”
Section: Discussionmentioning
confidence: 96%
“…A significant correlation has been found by some investigators (Williams et al 1959;Colbeck, 1960;Burke, 1963), but others (Rogers et al 1965;Browne et al 1959;Bullock et al 1964) have not. Williams et al (1959), Weinstein (1959), McNeill, Porter & Green (1961, Williams et al (1962), Ketcham et al (1962), Lindbom, Laurell & Grenvik (1967) and a, b) reported a higher incidence of wound sepsis among carriers, but Rogers et al (1965), Bullock et al (1964), Browne et al (1959, Lowden, Vaithilingham & Milne (1962), Bassett et al (1963 and Moore & Gardner (1963) did not find this to be true.…”
Section: Discussionmentioning
confidence: 96%
“…aureus isolated from the anterior nares, the main depot, closely resemble strains isolated from other skin sites (Williams et al 1959). In the case of sepsis, however, there is conflicting information as to whether the strains are derived from self-infection or crossinfection (Williams et al 1959;Bassett et al 1963). In the present study it would seem that both occurred and were responsible for the high isolation rate from skin sites.…”
Section: Discussionmentioning
confidence: 55%
“…The findings of the Torbay Hospital survey, as discussed in the foregoing pages, and of Bassett et al (1963), are in sharp contrast to those of the St Bartholomew's Hospital group (Williams et al 1962). In the Torbay Hospital study, the presence of a staphylococcus in the nose on admission to hospital was almost a guarantee of freedom from wound sepsis rather than a predisposing cause, and Bassett and his colleagues also report a lower incidence of wound sepsis in nasal carriers than in non-carriers.…”
Section: Discussionmentioning
confidence: 78%
“…Bassett et al (1963) interpret the findings of their two hospital surveys as indicating that self-infection of wounds was of minor importance, but that crossinfection probably occurred with equal frequency in carriers and non-carriers, the apparent excess of cross-infection in non-carriers being due to the impracticability of demonstrating cross-infection in carriers whose noses and wounds harboured the same phage type of staphylococcus. In the Torquay survey, however, the total incidence of sepsis in those who were staphylococcal nasal carriers on admission to hospital was so low that the existence of an increased resistance to sepsis in this group seems a reasonable inference.…”
Section: Discussionmentioning
confidence: 98%